Manajemen Kepala Madrasah dalam Meningkatkan Mutu Tenaga Pendidik di MTs NW Selayar - Sanjaya Perdana Zain (MANAZHIM, 2020)
Management as "the process of utilizing all resources that support Muslims, educational institutions and others, both hardware and software". Effective and effective to achieve certain goals. The headmaster is a leader who cannot be fulfilled by people without consent. Whoever is appointed to be the principal must be determined through certain procedures and requirements such as: educational background, experience, age, rank and integration. Therefore the madrasa head is essentially official, because the appointment is through a process and procedure in accordance with applicable regulations. Educators are professionals who are involved in the learning process, learning process, training and guidance, as well as conducting research and community service. Research using research in this study uses qualitative. In this question, the data related to the problem is discussed and published by the interpretive-interpretative. Madrasa head management in improving the quality of teaching staff in the MTs NW Selayar is carried out by involving educators in scientific forums (seminars, training, training, workshop and courses), further studies, MGMP revitalization, welfare benefits, providing support to access new information, buying books new policies that support the performance of educators and include teachers in the professional certificate program.